6,8-dihydroxy-7-methoxy-1-methyl-azafluorenone induces caspase-8- and -9-mediated apoptosis in human cancer cells - Ratana Banjerdpongchai (2018)
6,8-Dihydroxy-7-methoxy-1-methyl-azafluorenone (DMMA), a purified compound from Polyalthia cerasoides roots, is cytotoxic to various cancer cell lines. The aims of this study were to demonstrate the type of cancer cell death and the mechanism(s) involved. DMMA inhibited cell growth and induced apoptotic death in human leukemic cells (HL-60, U937, MOLT-4), human breast cancer MDA-MB231 cells and human hepatocellular carcinoma HepG2 cells in a dose dependent manner, with IC50values ranging between 20-55 μM. DMMA also decreased cell viability of human peripheral blood mononuclear cells. The morphology of cancer cells induced by the compound after staining with propidium iodide and examined under a fluorescence microscope was condensed nuclei and apoptotic bodies. Mitochondrial transmembrane potential (MTP) was decreased after 24h exposure in all five types of cancer cells. DMMA-induced caspase-3, -8, and -9 activity was strongly induced in human leukemic HL-60 and MOLT-4 cells, while in U937-, MDA-MB231- and HepG2-treated cells there was partial induction of caspase. In conclusion, DMMA-induced activation of caspase-8 and -9 resulted in execution of apoptotic cell death in human leukemic HL-60 and MOLT-4 cell lines via extrinsic and intrinsic pathways.